2011
DOI: 10.1021/bc2001159
|View full text |Cite
|
Sign up to set email alerts
|

Well-Controlled Cationic Water-Soluble Phospholipid Polymer−DNA Nanocomplexes for Gene Delivery

Abstract: The facile synthesis of biocompatible and nontoxic gene delivery vectors has been the focus of research in recent years due to the high potential in treating genetic diseases. 2-Methacryloxyethyl phosphorylcholine (MPC) copolymers were recently studied for their ability to produce nontoxic and biocompatible materials. The synthesis of well-defined and water-soluble MPC polymer based cationic vectors for gene delivery purposes was therefore attractive, due to the potential excellent biocompatibility of the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…23,30,40-42 In general, these copolymers, regardless of specific architecture and form of hydrophilic modification, show significantly decreased cytotoxicity and enhanced colloidal stability relative to their respective homopolymers. For example, MPC-AEMA and MPC-APMA copolymers showed low protein adsorption likely due to the zwitterionic MPC component.…”
Section: Polymer Functionalitiesmentioning
confidence: 99%
“…23,30,40-42 In general, these copolymers, regardless of specific architecture and form of hydrophilic modification, show significantly decreased cytotoxicity and enhanced colloidal stability relative to their respective homopolymers. For example, MPC-AEMA and MPC-APMA copolymers showed low protein adsorption likely due to the zwitterionic MPC component.…”
Section: Polymer Functionalitiesmentioning
confidence: 99%
“…In addition to the previous TE and KE biological studies, microscopic methods have been frequently used to visualize the level of % GFP expression inside the cells after MVCLs containing dendritic headgroups [72,121] or cyclen-based [120] lipids; (c) cationic polymers based on PEI and PAA derivatives [124,183], phospholipid-polymer [203], aminoacid-based [126,127,190], chitosan [204], PDMAEMA [133], dendrimers as PAMAM derivatives [132,201], others cationic polymer-type [107,164] or PEG-PPG-PEG/cyclodextrin polyrotaxanes [89]; and (d) polycations based on calixarenes [166,205] or cyclodextrins [106,136,142]. With respect to gene silencing/knockdown siRNA studies, micrographs and/or images have been reported for systems where the following gene vectors have been used: (a) MVCLs based on dendritic lipids [104]; and (b) cationic polymers based on dendrimers [199], diblock copolymers [105] or POEAA [144], last one in vivo studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The block copolymers and statistical copolymers of MPC and 2-aminoethyl methacrylamide hydrochloride (AEMA) were synthesized by reversible addition fragmentation chain transfer (RAFT) polymerization. The diblock copolymers showed better gene transfection efficiency as compared to the statistical copolymers [88]. PC modified PEI with different grafting levels were designed which can form polyplexes with DNA.…”
Section: Zwitterionic Nanocarriers For Gene Deliverymentioning
confidence: 99%